UJI ORGANOLEPTIK TEPUNG DAN BROWNIES BERBAHAN DASAR TEPUNG MOCAF (Modified Cassava Flour) TERFORTIFIKASI KALSIUM DARI CANGKANG TELUR AYAM RAS - Wulandari Meikawati; Agus Suyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
The dominance of wheat flour in the national food source map is very alarming. Imports ofwheat which amounts to millions of tons annually broad impact that caused the Indonesiannation has no longer self-sufficiency in food.MOCAF is a product of flour from cassava(Manihot esculenta Crantz) is processed by the principle of modifying the cells in thefermentation of cassava that has a whiter color than ordinary cassava flour and neutral flavor.Shell eggs is one of the calcium-containing waste is quite high, so it can be used as fortifikan ongroceries. This study aims to determine the level of preference and quality of the flour andflour-based brownies are fortified mocaf calcium from egg shells. MOCAF calcium fortifiedflour served in various concentrations of 0%, 5%, 10%, 15%, 20% and 25%. Organoleptic testwas conducted on 20 semi-trained panelists and analyzed deskkriptif. The results showed thatthe organoleptic value of wheat flour that includes color, tenderness and flavor of the highergrades mocaf organoleptic flour, flour brownies MOCAF  A level higher than wheat flourbrownies. and the average level of preference mocaf flour brownies with substitutes variationeggshell shell flour 5% -25% above the average level of preference wheat flour brownies.MOCAF flour brownies with egg shell shell flour substitution of 5% has the highest joy. Areception level brownies that include color, texture, flavor, aroma, and consistency of thebrownies tepungMOCAF above the level of preference of wheat flour brownies. Hedonic qualityassessment of wheat flour is higher than the hedonic quality MOCAF flour. The average valueof the hedonic quality of wheat flour brownies with ingredients lower if compared with flourMOCAFKey word: Organoleptic, Brownies, MOCAF